The Contribution of Muhammad Mahfuzh Al-Tarmasi to the Hadith Studies in Indonesia - Ali Masrur; Wawan Hernawan; Cucu Setiawan; Ayi Rahman (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This study examines the contribution of Mahfuzh Al-Tarmasi, Javanese-born scholars, who live in Mecca in Hadith studies in Indonesia. This study employs a qualitative method with a historical approach to trace al-Tarmasi contribution in Hadith studies in Indonesia. After analyzing the primary and secondary sources, this study shows that Mahfuzh Al-Tarmasi is one of the prominent Islamic scholars of Indonesia in the nineteenth century who have contributed greatly and significantly to the study of hadith and the science of Hadith (‘ilm al-riwāyat) in Indonesia. The contribution of Mahfuzh Al-Tarmasi can be seen by the fact that he had so many students who learned Hadith and the science of Hadith from him, not only from Indonesia but also from abroad such as Malaysia, India and other countries. He also produced works in the field of Hadith and the science of Hadith. Besides that, he had explained the book Alfiyyah Al-Suyūṭī by the title Manhaj Dhawī al-Nazhar: Sharḥ Manzhūmah ‘Ilm al-Āthār, a work containing science of Hadith, written only in four months. In this book, he had encreased twenty stanza poems to the book of Alfiyyah Al-Suyūṭī.